The Effectiveness of Court Administrative Systems in Promoting Transparency and Accountability in Judicial Institutions - Alvaro Reinn; Chealsea Reinn (Perkara : Jurnal Ilmu Hukum dan Politik, 2025)
This study is motivated by the growing demand for judicial bureaucratic reform that increasingly emphasizes transparency and accountability as the core pillars of modern judicial governance, in which administrative systems play a strategic role in supporting both principles. The objective of this research is to analyze the extent to which the effectiveness of court administrative systems contributes to enhancing transparency and accountability in judicial administrative practices, from the perspectives of both service users and court officials. This study employs a mixed-methods approach, combining quantitative data collected through questionnaires and qualitative data from semi-structured interviews, thereby enabling a more comprehensive understanding of the phenomenon under investigation. The findings indicate that effective administrative systems, characterized by clear procedures, timely service delivery, and well-organized documentation management, are positively associated with levels of transparency and accountability within judicial institutions, although challenges remain regarding implementation consistency and human resource readiness. Overall, this research provides a theoretical contribution by reinforcing the good governance framework in the context of judicial administration and offers practical insights for policymakers in formulating strategies to strengthen administrative systems. It concludes that improving administrative quality is a fundamental step in building public trust in transparent and accountable judicial institutions.